The Relationship of Social Media Addiction With Internet Use and Perceived Health: The Moderating Effects of Regular Exercise Intervention - Chen, Bo-Ching; Chen, Mei-Yen; Wu, Yu-Feng; Wu, Yu-Tai (Frontiers in Public Health, 2022)
The popularity of online social media in recent years has not only brought information and social convenience to people's lives, but has also given rise to many problems, among which social media addiction (SMA) has become a concern of many scholars and experts. Past research has shown that regular exercise (REx) can have many health benefits for the body, so numerous scholars and experts believe that this may be one possible strategy for reducing the health effects of online community addiction and Internet use (IU). Therefore, this study adopted a secondary data research approach to explore and predict the effect of age on social media use and personal health, and therefore included age as a control variable to investigate whether the intervention of REx, excluding the effect of age, moderates the effect of SMA on IU and on perceived health (PH). The participants of this study were adults aged 18 years or older in Taiwan, using the 2019 “Survey Research Data Archive,” Vol. 7, No. 5 data. A total of 1,933 questionnaires were retrieved, and after elimination of invalid responses, 1,163 data were analyzed using Partial Least Squares Structural Equation Modeling, PLS-SEM. The results were as follows: (1) SMA positively affected IU, (2) SMA could negatively affect PH, (3) there was no statistical effect of IU on PH, (4) SMA did not indirectly affect PH through IU, (5) REx had a moderating effect on SMA and IU, and (6) REx did not regulate the effect of SMA on PH. First, from these results, it is clear that the negative health effects of SMA may not be simply due to prolonged IU. Secondly, while it is true that the moderating effect for people with low levels of SMA can reduce IU, for people with high levels of SMA, the moderating effect of REx becomes a catalyst for increased Internet usage behavior. Finally, we draw conclusions based on the results of the study and propose directions and recommendations for follow-up research.